Penanaman Karakter Religius Melalui Metode Keteladanan Dalam Membentuk Kepribadian Siswa - Febria Saputra; Hilmiati Hilmiati; Ahmad Sulhan (Cordova Journal : languages and culture studies, 2020)
This research aims to find out 1) form of religious character through the teacher’s accuaracy ini shaping the student’s peersonality, 2) strategy in instilling religiuous character through the method accuray in shaping the personality of student’s. This research uses qualitative appoarch with descriptive method namely in describing or interpreting the circumstances of the problem to be examined using words instead of numbers. Data collection techiques in this study use observe the process of planting religious values in students, interviews to obtain data in the form of religious activities and strategies used instilling the value of religiousity to students, and documentation to obtain data in the form of vision and mission, infrstructure, human resources, and history of the esthablishment of MI Raudlatusshibyan NW Belencong. Data analysis techniques in this research through data reduction, data model, and data verification. Data sources obtained from principals, student, and teachers in MI Raudlatusshibyan NW Belencong. The result show that; 1) the for of religious character instillid through the method of nudity in shaping the personality of students is diligent in worshiping, serious in studing, having a moral attitude kharimah, and exempliying the attitude of teachers. 2) strategies in instilling religiuous character through in shaping student personalities are through reward and punishment, persuasive, rules and norms, and nudity. The conclusion of this research is religious character through the method of accuary in shaping the personality of student in MI Raudlatusshibyan NW Belencong by using various strategies in instilling it this very clearly presented and is appropriate to improve religiuous character in students.